THE IMPACT OF PRODUCT VARIATION, PRODUCT QUALITY, AND SERVICE QUALITY ON PURCHASE DECISION OF KO-KOPIAN PRODUCTS - Noah Jonathan Satria Wicaksono; J.E Sutanto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Abstract: The research which entitled "The Impact of Product Variation, Product Quality, and Service Quality on Purchase Decision of Ko-Kopian Products" has three objectives, that is, (1) knowing the impact of product variations on purchase decision of Ko-Kopian products, (2) knowing the impact of quality products on purchase decision of Ko-Kopian products, (3) knowing the impact of service quality on purchase decision of Ko-Kopian products. Ko-Kopian is a company that runs in the field of processed coffee beverage products. Product sale is carried out through offline store that is located in Cepu. This research uses quantitative method. The population that exists is the consumers who have bought and consumed products of Ko-Kopian. In this research, the sample that is used is 109 respondents. Data is collected through questionnaires that are distributed online. The data that is obtained is processed by using multiple linear regression analysis with SPSS program as helping tool. The results of this research are as follow: (1) Product variations have the effect significantly on purchase decision of Ko-Kopian products, (2) Product quality affects significantly on purchase decision of Ko-Kopian products, (3) Service Quality affects significantly on purchase decision of Ko-Kopian Products. Keywords: Product Variation, Product Quality, Service Quality